In vitro and in vivo activity of sodium houttuyfonate and sodium new houttuyfonate against Candida auris infection by affecting adhesion, aggregation, and biofilm formation abilities - Guangyuan Yang; Ruotong Yang; Xiaoxiao Zhu; Qianwen Xu; Xiaojia Niu; Chengui Miao; Wenfan Wei; Changzhong Wang; Tianming Wang; Daqiang Wu (Microbiology Spectrum)
ABSTRACT Candida auris is a rapidly spreading multidrug-resistant fungus that causes fatal infections under certain global conditions. Sodium houttuyfonate (SH) and sodium new houttuyfonate (SNH) are stable derivatives of houttuynin (decyl aldehyde) extracted from Houttuynia cordata, both possessing antifungal and antibacterial pharmacological activities. However, the inhibitory effects of SH and SNH on C. auris remain unclear. Therefore, this study aims to evaluate the potential activity and possible mechanisms of SH and SNH as antifungal agents against C. auris. First, our results showed that SH and SNH exhibit significantly inhibitory activity against fluconazole-resistant C. auris strains, but do not possess effective fungicidal activity. In addition, transcriptome and RT-qPCR studies revealed that SH and SNH can repress the expression of genes related to adhesion, aggregation, and biofilm formation. Next, we observed that SH and SNH can disrupt the adhesion and aggregation of early-stage C. auris. Furthermore, using the XTT assay, crystal violet staining, and confocal laser scanning microscopy, we found that the biofilm formation ability of C. auris was disrupted by SH and SNH. We also found that SH and SNH can potentially increase chitin content and expose β-1,3-glucan in the cell wall. Finally, infection models using Galleria mellonella larvae and mice with systemic candidiasis demonstrated that SH and SNH significantly inhibited the colonization and pathological damage of C. auris in vivo. Therefore, our presented results suggest that SH and SNH can effectively inhibit the growth, adhesion, aggregation, and biofilm formation to treat its colonization and pathological damage to the host of C. auris.IMPORTANCERecently, the annual proportion of non-C. albicans infections has been rising. The most notable characteristic of C. auris is its resistance to drugs, including multidrug resistance, which results in treatment failures and poses significant challenges in controlling its spread. Sodium houttuyfonate (SH) and sodium new houttuyfonate (SNH) are effective and stable derivatives of houttuynin (decyl aldehyde) extracted from traditional Chinese herbal medicine Houttuynia cordata, both possessing antifungal and antibacterial pharmacological activities. However, the inhibitory effects of SH and SNH on C. auris remain unclear. Through in vitro and in vivo approaches, we have demonstrated that SH and SNH can effectively inhibit the growth, adhesion, aggregation, and biofilm formation to treat its colonization and pathological damage to the host of C. auris. Thus, our findings provide new insights into possible options for clinical applications in the anti-C. auris.